Evaluation of IsoCal geometric calibration system for Varian linacs equipped with on‐board imager and electronic portal imaging device imaging systems. (8th May 2014) - Gao, Song; Du, Weiliang; Balter, Peter; Munro, Peter; Jeung, Andrew
Abstract : The purpose of this study is to evaluate the accuracy and reproducibility of the IsoCal geometric calibration system for kilovoltage (kV) and megavoltage (MV) imagers on Varian C‐series linear accelerators (linacs). IsoCal calibration starts by imaging a phantom and collimator plate using MV images with different collimator angles, as well as MV and kV images at different gantry angles. The software then identifies objects on the collimator plate and in the phantom to determine the location of the treatment isocenter and its relation to the MV and kV imager centers. It calculates offsets between the positions of the imaging panels and the treatment isocenter as a function of gantry angle and writes a correction file that can be applied to MV and kV systems to correct for those offsets in the position of the panels. We performed IsoCal calibration three times on each of five Varian C‐series linacs, each time with an independent setup. We then compared the IsoCal calibrations with a simplified Winston‐Lutz (WL)‐based system and with a Varian cubic phantom (VC)‐based system. The maximum IsoCal corrections ranged from 0.7 mm to 1.5 mm for MV and 0.9 mm to 1.8 mm for kV imagers across the five linacs. The variations in the three calibrations for each linac were less than 0.2 mm. Without IsoCal correction, the WL results showed discrepancies between the treatment isocenter and the imager center of 0.9 mm to 1.6 mm (for the MV imager) and 0.5 mm to 1.1 mm (for the kV imager); with IsoCal corrections applied, the differences were reduced to 0.2 mm to 0.6 mm (MV) and 0.3 mm to 0.6 mm (kV) across the five linacs. The VC system was not as precise as the WL system, but showed similar results, with discrepancies of less than 1.0 mm when the IsoCal corrections were applied. We conclude that IsoCal is an accurate and consistent method for calibration and periodic quality assurance of MV and kV imaging systems. PACS numbers: 87.55.Qr, 87.56.Fc